Judicial review and religious values - Vorster, N (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article discusses the inherent propensity of a Constitutional State to degenerate into a legalistic society where jurisprudence exercises the same kind of power that religion exercised in medieval theocratic societies. The first part of the article identifies such developments in South African Constitutional jurisprudence. Examples are cited where Courts have imposed a liberal understanding of rights on society, imposed values on South African society that are alien to most South Africans, and relegated religion to the private sphere of life. In the second part of the article some suggestions are made for ways in which this can be prevented. The article concludes that measures must be introduced to restrain the power of courts. Conversely it is important that Christian theologians and philosophers translate Christian values to the public realm in a juridical applicable way.